The Effect of Walking Lunges and Squat Side Kick Exercises on Mawashi Geri Kick Speed in Inkanas Karate Athletes Aged 13-15 Years, UNM Makassar Branch (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The purpose of this study was to compare the effectiveness of double-leg hurdle jumps and single-leg hurdle jumps in increasing the shooting speed of soccer players at SMPN 3 Bontomarannu. This study aimed to determine the effect of walking lunges and squat side kick exercises on the speed of mawashi geri kicks in INKANAS karate athletes aged 13-15 years at the UNM Makassar branch. This study is an experimental study. The population of this study was 24 Inkanas karate athletes aged 13-15 years at the UNM Makassar branch. The research sample was 24 Inkanas karate athletes aged 13-15 years at the UNM Makassar branch. The data analysis technique used inferential testing on t-test statistics. The results of the study showed that 1) there was an effect of walking lunges training on the speed of mawashi geri kicks in Inkanas karate athletes aged 13-15 years at the UNM Makassar branch. This can be seen from the results of the analysis obtained a t-value of -8.074 with a probability (sig) = 0.000 smaller than 0.05. 2) there is an effect of squat side kick training on the speed of mawashi geri kicks in Inkanas karate athletes aged 13-15 years at the UNM Makassar branch. This can be seen from the results of the analysis obtained a t-value of -12.318 with a probability (sig) = 0.000 smaller than 0.05. 3) there is an effect of walking lunges and squat side kick training that is better on the speed of mawashi geri kicks in Inkanas karate athletes aged 13-15 years at the UNM Makassar branch. This can be seen from the results of the analysis obtained a t-value of -1.381 with a probability (sig) = 0.040 smaller than 0.05. In addition, seen from the average difference between the two exercise groups where the average value is 25.75 (walking lunges exercise) and 28.50 (squat side kick exercise). Conclusion Squat side kick exercise is better than walking lunges exercise on mawashi geri kick speed in INKANAS karate athletes aged 13-15 years, UNM Makassar branch.